PENGARUH PROMOSI JABATAN, PENGEMBANGAN SUMBER DAYA MANUSIA DAN KEMAMPUAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA HOTEL DANAU TOBA INTERNATIONAL MEDAN - Elyas, Richard; Pardede, Erwin; Lumban Gaol, Jonner (JURNAL PROINTEGRITA, 2020)
Productivity can be influenced by many factors, including work discipline, training, work motivation, job promotion; human resource development and work ability but the most important factors are promotion, development of human resources and work ability. This study aims at finding the effect of job promotion, human resource development and work ability partially and simultaneously on the work productivity of employees at Hotel Danau Toba International Medan. The population of this research is 600 workers. To determine the number of samples, the Slovin formula was used so that the sample is 86 workers. Data collection techniques in this study are questionnaires, interviews and documentation studies while the data analysis technique used is the classical assumption test, multiple regressions, t test, F test and the coefficient of determination. The results show that the job promotion variable has a significant effect on work productivity at the Danau Toba International Medan Hotel, where the better the promotion, the higher the employee's work productivity. HR development variables have a significant effect on work productivity at the Danau Toba International Hotel Medan, where the better the HR development, the higher the employee's work productivity. The work ability variable has a significant effect on work productivity at the Danau Toba International Medan Hotel, where the better the work ability, the higher the employee's work productivity. Simultaneously there is a significant influence on job promotion variables, HR development and work ability. It is suggested that hotels need to carry out job promotions based on work competence and work performance, so that employees who have high work abilities and performance are prioritized for promotion. Hotels need to adapt the development program to the long-term development plan, and determine development program participants based on the potential of individual employees' abilities. Hotels need to place employees according to their educational background and work experience.